2022
DOI: 10.1029/2021ef002240
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Socioeconomic Exposure to Heatwaves in South Asia Under Changing Climate

Abstract: The risk of population exposure to severe heatwaves (HWs) increases in a hot and humid environment (Im et al., 2017). The wet-bub temperature (T WB ) takes into account temperature and humidity to measure the human body's surveillance limits. Population exposure to T WB exceeding a threshold of 35°C for a few hours of a day would result in death; therefore, 35°C can be used as an upper limit on human surveillance in a natural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 90 publications
5
37
0
Order By: Relevance
“…Interestingly, the present study also witnessed increasing trends of warm temperature events in the southwestern and northeastern parts of the regions, which agreed with the findings of previous studies in the same regions [51,52]. The upsurge of frequency, intensity, and extent of daily warm extreme temperature and decline of extreme cold temperature may occur in parts of the world, resulting in the escalation of length and intensity of warm period or a heatwave in most land areas [3,5,53,54].…”
Section: Observed Annual and Seasonal Trends Of Precipitation And Tem...supporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, the present study also witnessed increasing trends of warm temperature events in the southwestern and northeastern parts of the regions, which agreed with the findings of previous studies in the same regions [51,52]. The upsurge of frequency, intensity, and extent of daily warm extreme temperature and decline of extreme cold temperature may occur in parts of the world, resulting in the escalation of length and intensity of warm period or a heatwave in most land areas [3,5,53,54].…”
Section: Observed Annual and Seasonal Trends Of Precipitation And Tem...supporting
confidence: 92%
“…The time series revealed abrupt drying patterns with intensified droughts from 2000 to 2020 in R-1 and R-2, whereas R-3 observed a relatively less drying trend, and R-4 even showed a wetting trend over the 40-year period. Similar findings were reported in previous studies over the regions [3,5]. The previous works attributed the regional drying to the warming climate and/or fewer changes in precipitation.…”
Section: Observed Drought Trends Over Space and Timesupporting
confidence: 91%
See 1 more Smart Citation
“…Shahzaman et al [ 87 ] concluded in their study that drought has been observed over central and northern Pakistan during 1982–2019 by integrating various data types. Proportion of South Asian population exposer to heatwaves is increasing under the shared socioeconomic scenarios in the twenty first century, however, the northern areas of Pakistan are unaffected presently [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that the growth environment and growth of grasslands are determined by precipitation and air temperature, and the changes in precipitation and air temperature play a vital role in the change in plant productivity of grasslands all over the world [8]. However, with the increase in population, the influence of human activities such as overgrazing, on grassland becomes more and more obvious [9][10][11][12]. So far, there have been a lot of studies on grassland NPP as an indicator to measure the impact of climate change and human activities on grassland ecosystems.…”
Section: Introductionmentioning
confidence: 99%